Solid Additives for Improving the Performance of Sulfur Cathodes in Lithium–Sulfur Batteries—Adsorbents, Mediators, and Catalysts. Issue 6 (12th February 2020) - Ye, Hualin; Lee, Jim Yang
Abstract: Lithium–sulfur (Li–S) batteries, with high theoretical energy density and the low cost of sulfur, have the most appeal as the successor to lithium‐ion batteries. Their performance to date is however undermined by the redox shuttling of dissolved polysulfides between the cathode and anode during battery cycling. Though substantial improvements are made with the use of solid additives, which are described in the literature as adsorbents, mediators, or catalysts for the sulfur cathodes, it is still a challenge to differentiate the specific functions suggested by their names due to the incomplete understanding of the 16‐electron sulfur electrochemical reaction. Here the research on solid additives in the development timeline of Li–S batteries is reviewed, and some perspectives on the deployment method are provided which can optimize the performance of solid additives (catalysts, in particular) in Li–S batteries. Abstract : The high energy density and low cost of sulfur have positioned lithium–sulfur batteries well as a lithium‐ion battery successor. The loss of electrochemically active sulfur from the cathode is still a prevailing challenge. This essay is an account of the prospects of solid electrode additives (adsorbents, mediators, and catalysts) as a technology solution, and some needed areas for further research.